2014
DOI: 10.1097/jfn.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Client Satisfaction With Nursing-led Sexual Assault and Domestic Violence Services in Ontario

Abstract: The high uptake and positive evaluation of services provided by Ontario's Sexual Assault/Domestic Violence Treatment Centre programs confirms the value of nursing-led, hospital-based care in the aftermath of sexual assault and domestic violence. Ongoing evaluation of such services will ensure the best care possible for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 6 publications
0
61
0
2
Order By: Relevance
“…For instance, immediate and later healthcare experiences were sometimes distressing to participants in this study because they felt mistreated by providers. Similarly, some participants in Du Mont and colleagues' () study on the emergency care experiences of sexual abuse survivors reported feeling disrespected or mistreated by the ED staff. However, the vast majority of participants (95%) in that study indicated that they felt respected, believed, supported and cared for by emergency care nurses and physicians (Du Mont et al., ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, immediate and later healthcare experiences were sometimes distressing to participants in this study because they felt mistreated by providers. Similarly, some participants in Du Mont and colleagues' () study on the emergency care experiences of sexual abuse survivors reported feeling disrespected or mistreated by the ED staff. However, the vast majority of participants (95%) in that study indicated that they felt respected, believed, supported and cared for by emergency care nurses and physicians (Du Mont et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, some participants in Du Mont and colleagues' () study on the emergency care experiences of sexual abuse survivors reported feeling disrespected or mistreated by the ED staff. However, the vast majority of participants (95%) in that study indicated that they felt respected, believed, supported and cared for by emergency care nurses and physicians (Du Mont et al., ). It is possible that the interview prompts used in the current study (“Please tell me about a difficult healthcare experience.”) biased participants' responses towards negative healthcare experiences.…”
Section: Discussionmentioning
confidence: 95%
“…Systematic collection and use of DNA evidence could contribute to increased prosecution, but generally has not thus far, as Du Mont and White () have noted that forensic evidence is infrequently utilized by the criminal justice system in sexual assault cases. Rape survivors endure an invasive, often degrading, full‐body medical exam (Bumiller 2009; Corrigan ; Quinlan et al ; cf: Campbell et al ; Du Mont et al ; Fehler‐Cabral et al )—and often nothing happens with the evidence collected. As cities throughout the United States are uncovering large stockpiles of untested SAKs, these discoveries re‐open conversation about how forensic DNA testing could help sexual assault investigations and prosecutions.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have questioned whether these actions are indeed indicative of a desire for criminal justice system involvement because current North American systems of post‐assault care specifically direct victims to these services (e.g., victims are told to have a medical forensic rape exam) (Bumiller 2009; Corrigan ; Parnis & Du Mont ; Quinlan et al ). Empirical studies on this issue find that victims seek post‐assault medical care for myriad reasons—for healthcare, for emotional support and advocacy, for forensic evidence collection, and/or for reporting to the police (Du Mont et al ; Patterson & Campbell ).…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, 1,136 individuals (or their guardians) who presented with a report of sexual abuse/assault agreed to participate in the evaluation of services (Du Mont et al, 2014). Fifty-eight, were children aged 11 years and younger; 16.4% were less than 3 years old, 38.2% were 3-5 years old, 23.6% were 6-8 years old, and 21.8% were 9-11 years old.…”
Section: ▪ Description Of the Casesmentioning
confidence: 99%